Cost-effectiveness of teduglutide in pediatric patients with short bowel syndrome: Markov modeling using traditional cost-effectiveness criteria. Issue 1 (6th October 2020) - Raghu, Vikram Kalathur; Rudolph, Jeffrey A; Smith, Kenneth J
ABSTRACT: Background: Teduglutide use in pediatric patients with short bowel syndrome can aid in the achievement of enteral autonomy, but with a price of >400, 000 per y. Objective: The current study evaluated the cost-effectiveness of using teduglutide in conjunction with offering intestinal transplantation in US pediatric patients with short bowel syndrome. Design: A Markov model was used to evaluate the costs (in US dollars) and effectiveness [in quality-adjusted life years (QALYs)] of using teduglutide compared with offering intestinal transplantation. Parameters were estimated from published data where available. The primary effect modeled was the probability of weaning from parenteral nutrition while on teduglutide. Sensitivity analyses were performed on all model parameters. Results: Compared with offering only intestinal transplantation, adding teduglutide cost $ 124, 353/QALY gained. Reducing the cost of the medication by 16% allowed the cost to reach the typical benchmark of $ 100, 000/QALY gained. Probabilistic sensitivity analysis favored transplantation without offering teduglutide in 68% of iterations at a $ 100, 000/QALY threshold. Never using teduglutide created an opportunity cost of over $ 100, 000 per patient. Conclusions: At its current price, teduglutide does not provide a cost-effective addition to transplantation in the treatment of pediatric short bowel syndrome. Further work should look to identify cost-reducing strategies, including alternative dosing regimens.